Two equivalent expressions to 7x + 1 are:
1) 1 + 7x
2) x + x + x + x + x + x + x + 1 (which is the expanded form of 7x + 1)
Which two expressions are equivalent to 7x+1
5 answers
What else?
In addition to the previous two expressions, there are many other expressions that are equivalent to 7x + 1. Here are a few examples:
3) 7(x + 1)
4) 7x + 2 - 1
5) (6x + 1) + x
6) 8x - x + 1
7) 7x + (4 - 3)
8) 14x/2 + 1
9) (7/1)x + 1
10) 2(3.5x) + 1
These are just a few possibilities, as there are countless ways to manipulate the expression 7x + 1 to obtain an equivalent one.
3) 7(x + 1)
4) 7x + 2 - 1
5) (6x + 1) + x
6) 8x - x + 1
7) 7x + (4 - 3)
8) 14x/2 + 1
9) (7/1)x + 1
10) 2(3.5x) + 1
These are just a few possibilities, as there are countless ways to manipulate the expression 7x + 1 to obtain an equivalent one.
A. 2(2x−1)+3(x+1)
B. 5(x+1)+2(x−2)
C. 7(x−1)+2
D. 7(x−1)+3
B. 5(x+1)+2(x−2)
C. 7(x−1)+2
D. 7(x−1)+3
Among the given expressions, expressions A, B, C, and D are not equivalent to 7x + 1. However, we can simplify and expand each expression to determine if they are equivalent:
A. 2(2x−1)+3(x+1) = 4x - 2 + 3x + 3 = 7x + 1 (equivalent to 7x + 1)
B. 5(x+1)+2(x−2) = 5x + 5 + 2x - 4 = 7x + 1 (equivalent to 7x + 1)
C. 7(x−1)+2 = 7x - 7 + 2 = 7x - 5 (not equivalent to 7x + 1)
D. 7(x−1)+3 = 7x - 7 + 3 = 7x - 4 (not equivalent to 7x + 1)
So, expressions A and B are equivalent to 7x + 1, while expressions C and D are not equivalent.
A. 2(2x−1)+3(x+1) = 4x - 2 + 3x + 3 = 7x + 1 (equivalent to 7x + 1)
B. 5(x+1)+2(x−2) = 5x + 5 + 2x - 4 = 7x + 1 (equivalent to 7x + 1)
C. 7(x−1)+2 = 7x - 7 + 2 = 7x - 5 (not equivalent to 7x + 1)
D. 7(x−1)+3 = 7x - 7 + 3 = 7x - 4 (not equivalent to 7x + 1)
So, expressions A and B are equivalent to 7x + 1, while expressions C and D are not equivalent.